789. Viral and Immunologic biomarkers of COVID-19 improve risk stratification and identify patients most likely to benefit from therapy with remdesivir. (15th December 2022) - Singh, Kanal; Rubenstein, Kevin; Callier, Viviane; Shaw-Saliba, Katy; Rupert, Adam; Dewar, Robin L; Laverdure, Sylvain; Highbarger, Helene; Lallemand, Perrine; Huang, Meei-Li; Jerome, Keith R; Sampoleo, Reigran; et al.
Abstract: Background: ACTT-1 demonstrated clinical efficacy of remdesivir (RDV) in hospitalized patients with COVID-19; subgroup analyses suggested those most likely to benefit presented with milder clinical illness. To further clarify what subsets of hospitalized patients might benefit from RDV, we analyzed virological and immunological biomarkers in this previously reported cohort. Methods: Serum and upper respiratory tract (URT) swabs were collected on Day 1, 3, 5, 8, and 11 while hospitalized; Day 15 and 29 as able were collected and tested for quantitative RNA (URT and plasma), serum nucleoprotein (NPR), IL-6, CRP through Day 6, and serostatus (baseline only). Participants with a baseline and at least one subsequent sample were used in this analysis. Associations of all these biomarkers with clinical outcomes (mortality, recovery) and response to therapy were assessed. Of the 1062 participants in ACTT-1, 642 had baseline and at least one subsequent sample within 6 days of randomization (Fig 1, Table 1). Results: RDV-treated patients with moderate/severe disease who had elevated baseline NPR levels recovered faster (RRR 1.95 vs 1.04, p = 0.01); similar trends were noted for plasma and URT RNA levels (Fig 2A); mortality treatment effects by viral load subgroups (high or low) were not seen (Fig 2B). In patients with less severe illness, RDV treatment was associated with an accelerated decline in NPR ( difference -0.062 log10 pg/ml per day, p = 0.003) and plasma RNA levels (difference -0.040 log10 pg/ml per day, p = 0.004. Fig 3A), and a decrease in the proportion of patients with increasing and/or persistent viral loads (Fig 3B). Patients with increasing/persistent viral loads also took longer to recover than those with decreasing viral loads, irrespective of disease severity: RRR for plasma RNA 0.45, 95% CI 0.28–0.73, RRR for NPR 0.44, 95% CI 0.22–0.88 for moderate/severe disease; RRR for plasma RNA 0.26, 95% CI 0.10 – 0.70, RRR for NPR n.e. (no recoveries) for critical disease (Fig 4). Conclusion: Our study demonstrates a systemic antiviral effect of remdesivir, shows the prognostic value of viral and immunologic biomarkers for mortality and failure to recover, and identifies a group of hospitalized patients with COVID-19 most likely to benefit from remdesivir treatment. Disclosures: Kevin Rubenstein, MS, Frederick National Laboratory: Funded by the NCI Contract No. 75N91019D00024 Viviane Callier, PhD, Frederick National Laboratory: Funded by the NCI Contract No. 75N91019D00024 Adam Rupert, n/a, Frederick National Laboratory: Funded by the NCI Contract No. 75N91019D00024 Robin L. Dewar, PhD, Frederick National Laboratory: Funded by the NCI Contract No. 75N91019D00024 Sylvain Laverdure, n/a, Frederick National Laboratory: Funded by the NCI Contract No. 75N91019D00024 Helene Highbarger, n/a, Frederick National Laboratory: Funded by the NCI Contract No. 75N91019D00024 Perrine Lallemand, n/a, Frederick National Laboratory: Funded by the NCI Contract No. 75N91019D00024 Danielle P. Porter, PhD, Gilead: Stocks/Bonds Kavita Juneja, n/a, Gilead Sciences: Employee Alexander L. Greninger, MD, PhD, Abbott: Contract testing|Cepheid: Contract testing|Gilead: Grant/Research Support|Hologic: Contract testing|Janssen: Contract testing|Merck: Grant/Research Support|Novavax: Contract testing|Pfizer: Contract testing.